Delayed Sternal Closure Using a Vacuum-Assisted Closure System in Adult Cardiac Surgery - Hyun Ah Lim; Jinwon Shin; Min Seop Jo; Yong Jin Chang; Deog Gon Cho; Hyung Tae Sim (Journal of Chest Surgery, 2023)
Background: Delayed sternal closure (DSC) is a useful option for patients with intractable bleeding and hemodynamic instability due to prolonged cardiopulmonary bypass and a preoperative bleeding tendency. Vacuum-assisted closure (VAC) has been widely used for sternal wound problems, but only rarely for DSC, and its efficacy for mediastinal drainage immediately after cardiac surgery has not been well established. Therefore, we evaluated the usefulness of DSC using VAC in adult cardiac surgery. Methods: We analyzed 33 patients who underwent DSC using VAC from January 2017 to July 2022. After packing sterile gauze around the heart surface and great vessels, VAC was applied directly without sternal self-retaining retractors and mediastinal drain tubes. Results: Twenty-one patients (63.6%) underwent emergency surgery for conditions including type A acute aortic dissection (n=13), and 8 patients (24.2%) received postoperative extracorporeal membrane oxygenation support. Intractable bleeding (n=25) was the most common reason for an open sternum. The median duration of open sternum was 2 days (interquartile range [25th–75th pertentiles], 2–3.25 days) and 9 patients underwent VAC application more than once. The overall in-hospital mortality rate was 27.3%. Superficial wound problems occurred in 10 patients (30.3%), and there were no deep sternal wound infections. Conclusion: For patients with an open sternum, VAC alone, which is effective for mediastinal drainage and cardiac decompression, had an acceptable superficial wound infection rate and no deep sternal wound infections. In adult cardiac surgery, DSC using VAC may be useful in patients with intractable bleeding or unstable hemodynamics with myocardial edema.